Analisis Pemahaman Masyarakat Mengenai Dagusibu Obat di Desa Larangan Pamekasan - Adinugraha Amarullah; Farida Anwari; Bella Fevi Aristia; Ivan Charles Seran; Hamidah, Hamidah (INSOLOGI: Jurnal Sains dan Teknologi, 2025)
Medicine is an essential part of daily life, yet public knowledge regarding safe medication management often falls short of health standards. To address this issue, the Indonesian Pharmacists Association (Ikatan Apoteker Indonesia, IAI) launched the DAGUSIBU educational program (Obtain, Use, Store, Dispose) to enhance understanding of proper medication management. This study aims to assess the level of knowledge among the residents of Larangan Dalam Village, Larangan District, Pamekasan Regency regarding the DAGUSIBU principles and identify factors influencing their understanding. The study employs a quantitative descriptive approach using purposive sampling techniques, involving 98 respondents from a total population of 3,303 aged 17 to 60 years. Data were collected through a questionnaire covering demographic variables and questions about procedures for obtaining, using, storing, and disposing of medications according to IAI guidelines. Analysis was conducted using the Guttman scale to classify knowledge into three categories: good, moderate, and poor. The results reveal that 42.9% of respondents have good knowledge, 36.7% have moderate knowledge, and 20.4% have poor understanding of medication management. These findings highlight the importance of enhancing health education and strategic interventions to optimize medication management at the household level and prevent the risks of misuse and negative health impacts. The recommendations based on this study are expected to serve as a reference for healthcare institutions and related organizations in designing effective intervention programs.